2021
DOI: 10.1186/s13063-021-05168-x
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal flap for lymphocele prophylaxis following robotic-assisted laparoscopic radical prostatectomy with pelvic lymph node dissection: study protocol and trial update for the randomized controlled PELYCAN study

Abstract: Background Data from interventional studies suggest that a peritoneal flap after pelvic lymph node dissection (LND) during laparoscopic, robotic-assisted radical prostatectomy (RARP) may reduce the rate of symptomatic lymphoceles in transperitoneal approach. However, most of these studies are not conducted in a randomized controlled fashion, thus limiting their scientific value. A recent prospective, randomized, controlled trial (RCT) did not show superiority of a peritoneal flap while further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Both authors reported a reduction in the incidence of symptomatic lymphocele formation with the use of their techniques. [ 10 13 ] However, Brundl et al . performed a randomized controlled trial to study the efficacy of Lebeis’ technique in patients undergoing conventional RARP and did not find any significant difference in the lymphocele incidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both authors reported a reduction in the incidence of symptomatic lymphocele formation with the use of their techniques. [ 10 13 ] However, Brundl et al . performed a randomized controlled trial to study the efficacy of Lebeis’ technique in patients undergoing conventional RARP and did not find any significant difference in the lymphocele incidence.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 7 8 9 ] Among these, the use of peritoneal flaps have emerged as a promising novel technique to tackle this complication. [ 10 11 12 13 ] However, there is sparse literature on the use of this technique in Retzius-sparing RARP. Therefore, we developed a peritoneal distraction technique and aimed to assess its impact on lymphocele formation in Retzius-sparing RARP group.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the available literature, the likelihood of lymphocysts following PLND varies between 1.3% and 25% [38][39][40], and their presence is not solely attributed to the enlargement of PLND excision [38,41], but also to advanced age, elevated BMI (Body Mass Index), and a past occurrence of peripheral vascular/lymphatic lesions [41][42][43][44]. To reduce the number of lymphocysts, preventive measures such as constructing a peritoneal flap [45,46]、peritoneal opening [47,48], elastic clamping of lymphatic vessels [39], bipolar electrocoagulation of the trauma, and spraying of haemostatic powder [49] can be taken during operation. Nevertheless, lymphocysts do not consistently manifest symptoms, and interventions are typically limited to symptomatic lymphocysts (such as excessive abdominal-pelvic effusion or secondary infections).…”
Section: Surgical Complicationsmentioning
confidence: 99%
“…In the future, the results of another ongoing RCT (Pelycan) should clarify the benefits of PIF in preventing SLC. [40]…”
Section: Study Selection Bias Performance Bias Detection Bias Attriti...mentioning
confidence: 99%